A Configurational Approach to Model Triglyceride Pure Component Properties. Issue 10 (24th June 2021) - Seilert, Julia; Flöter, Eckhard
Abstract: In this contribution, a new model to predict the thermodynamic properties, namely enthalpy of fusion (Δ H f ) and melting temperature ( T m ), of pure triglycerides (TAGs) is presented. Different contributions to these properties could be expressed by means of repetitive structural attributes deduced from molecular structures. Carefully formulated configurational and geometrical simplifications enabled to attribute physical meaning to most of the parameters. Overall, the number of adjustable parameters is successfully minimized to less than half compared to the well‐known model proposed by Wesdorp in "Liquid‐multiple solid phase equilibria in fats: theory and experiments" (1990). Comparing both models revealed that the new model surpasses the reference model considering desirable prediction quality, thermodynamical consistency, and the number of adjustable parameters. Practical application : The successful description of the phase behavior of TAG mixtures is crucial to understand complex phenomena in fat‐based products. This objective is based on reliable predictions of pure component properties and non‐ideal mixing in liquid‐ and solid‐phases. The newly formulated model gives reliable descriptions of experimental data and predictions of unknown data of TAGs — both thermodynamically consistent. Those are of benefit as prerequisite for any meaningful effort to predict the solid‐liquid phase behavior of TAG mixtures as well as crystallization kinetics. Abstract : Geometrical simplification of subcell packing to estimate the average distance between adjacent fatty acids in three polymorphic forms and reference cell to describe the triglyceride lateral crystal packing (here: double chain length crystal structure). For the approximation of the thermodynamic properties, three main contributions are accounted for: methyl end plane, glycerol moiety, and lateral interaction.